The Influence of Health Education about Handling Choking on Children through Booklet Media on the Knowledge Level of Posyandu Cadres in Karangsari Village - Anggun - Sulistiyani; Meida Laely Ramdani (Jurnal Ilmiah Keperawatan Indonesia [JIKI], 2020)
Background: Choking deserves attention because it often happens to children. The inappropriate handling of choking becomes a vigilance. Caution and handling of choking become crucial even to cadres of Posyandu (the centre for pre- and post-natal health care and information for women and for children under five) in Karangsari Village. Thus, providing them with health education is necessary.Objective: To identify the influence of health education about handling choking on children through booklet media on the knowledge level of Posyandu cadres in Karangsari Village.Research Methods: This is a quantitative research using pre-experimental design with one group pre-test and post-test design approach. The research sample was taken through a total sampling technique. There were 30 cadres fulfilling the inclusion and exclusion criteria. The research instrument consists of pre and post-test questionnaire, which was modified and had been tested for its validity and reliability.Research Result: The research result indicates that the knowledge average value obtained by the 30 respondents before being given health education is 61.50 and after being given health education is 88.00. The result of bivariate analysis using t-test sample paired test shows the p-value of 0.0001.Conclusion: There is an influence of health education about handling choking on children through booklet media on the knowledge level of Posyandu cadres in Karangsari Village.